Penerapan Sanksi Pidana Adat Perzinaan di Nagari Koto Tinggi Berdasarkan Hukum Adat Salingka Nagari - Harfiani, Putri Salsa; Zurnetti, Aria (Lareh Law Review, 2025)
Customary law in Indonesia is recognized by the state, even though it is unwritten, and it develops from community customs governed by norms passed down through generations. This is stipulated in Articles 18B and 28I of the 1945 Constitution. Customary criminal law regulates offenses with sanctions such as fines, expulsion, or other punishments, as seen in the Minangkabau customary law related to criminal acts such as adultery. The resolution of customary criminal cases is carried out through deliberation and supervision by customary leaders. In Minangkabau, customary criminal law is known as "Undang-Undang Nan Salapan" (material law) and "Undang-Undang Nan Duo Puluah" (procedural law). In Nagari Koto Tinggi, although subject to national law, Minangkabau customary criminal law is still enforced. The issues raised are: 1) what types of customary violations have been sanctioned against adulterers in Nagari Koto Tinggi based on the Customary Law of Salingka Nagari? 2) What is the procedure for resolving customary criminal cases and the imposition of sanctions on customary law offenders in Nagari Koto Tinggi? and 3) What are the challenges and efforts to overcome obstacles in the implementation of Minangkabau customary sanctions in Nagari Koto Tinggi? This empirical legal research collects data from interviews and direct observation. In Nagari Koto Tinggi, customary violations are resolved by the Customary Peace Council through stages of "cemo," "tuduh," and the imposition of sanctions such as fines or expulsion. The dispute resolution emphasizes consensus and aims to restore social balance. Despite challenges in adapting customary law to modern developments, collaboration between customary institutions and the government, as well as the adjustment of cultural values, is key to the sustainability of customary law in the future. Keywords : General Meeting of Shareholders, Limited Liability Company, Notary